2023
DOI: 10.1101/2023.01.26.23285029
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating the causal relationship between educational attainment and mental health

Abstract: We investigate the causal relationship between educational attainment (EA) and mental health using two research designs. First, we compare the relationship between EA and seventeen psychiatric diagnoses within sibship in Dutch national registry data (N = 1.7 million), controlling for unmeasured familial factors. Second, we use two-sample Mendelian Randomization, which uses genetic variants related to EA or psychiatric diagnosis as instrumental variables, to test whether there is a causal relation in either dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 73 publications
(102 reference statements)
3
9
0
Order By: Relevance
“…The cognitive PGS was also associated with decreased odds of an ADHD diagnosis and lower psychotic-like experience (PLE) severity scores, but greater risk for anorexia. This latter finding is generally in line with work showing a positive association between cognitive performance and educational attainment and anorexia (Demange et al, 2023; THE BRAINSTORM CONSORTIUM et al, 2018; Watson et al, 2019), while the correlation with lower severity of PLEs is highly consistent with other work showing PLEs to be related to decreased school performance (Davies et al, 2018; Villa et al, 2023) and general cognitive deficits (e.g., executive functioning; Sheffield et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…The cognitive PGS was also associated with decreased odds of an ADHD diagnosis and lower psychotic-like experience (PLE) severity scores, but greater risk for anorexia. This latter finding is generally in line with work showing a positive association between cognitive performance and educational attainment and anorexia (Demange et al, 2023; THE BRAINSTORM CONSORTIUM et al, 2018; Watson et al, 2019), while the correlation with lower severity of PLEs is highly consistent with other work showing PLEs to be related to decreased school performance (Davies et al, 2018; Villa et al, 2023) and general cognitive deficits (e.g., executive functioning; Sheffield et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…Considering previous inconsistent evidence of a protective effect of education on mental disorders,47 we conducted supplementary post hoc MVMR analyses to assess the potential role of cognitive ability in the positive association found between genetic liability to EA and the risk of SCZ and BD. We found that the direct effect of EA on the risk of BD and SCZ, not mediated through cognitive ability, was larger than that found in the original model (MVMR-ORSCZ=3.95 per-SD-increase, p=4.55E–09; IVW-ORBIP=2.73, p=1.470E–06).…”
Section: Resultsmentioning
confidence: 99%
“…However, our study also has several limitations. First, recent studies have highlighted that MR analyses and SES phenotypes may be affected by assortative mating, dynastic effects, participation bias and design assumptions 47 68–71. There is also a limitation in the characterisation of complex phenotypes such as intelligence or income in the GWAS studies.…”
Section: Discussionmentioning
confidence: 99%
“…College education also increases opportunities for jobs with benefits like health coverage and increased access to health-promoting knowledge and resources, resulting in lower rates of death and longer lives. 9 Lower levels of educational attainment are associated with increased risk of some psychiatric diagnoses like Major Depressive Disorder and Generalized Anxiety Disorder 33 and higher rates of suicide. 34 Conversely, poor mental health is associated with higher risk of early termination of education, limiting educational attainment.…”
Section: Discussionmentioning
confidence: 99%